2023
DOI: 10.3390/molecules28062551
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Study on the Structure, Bioactivity, and Silver Adsorption of Silk Fibroin Fibers Grafted with Methacrylonitrile

Abstract: Natural fibers have received increasing attention as starting materials for innovative applications in many research fields, from biomedicine to engineering. Bombyx mori silk fibroin has become a material of choice in the development of many biomedical devices. Grafting represents a good strategy to improve the material properties according to the desired function. In the present study, Bombyx mori silk fibroin fibers were grafted with methacrylonitrile (MAN) with different weight gains. The potential interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Both degumming methods remove the existing sericin; however, SEM images show increased fibrillar damage in chemically degummed SW and DC. Previous studies have reported similar results when comparing these degumming methods, indicating that chemical degumming may cause hydrolytic degradation of proteins 21 , 22 .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Both degumming methods remove the existing sericin; however, SEM images show increased fibrillar damage in chemically degummed SW and DC. Previous studies have reported similar results when comparing these degumming methods, indicating that chemical degumming may cause hydrolytic degradation of proteins 21 , 22 .…”
Section: Discussionsupporting
confidence: 55%
“…Raw material comparisons showed differences in β-turn and side chains, corresponding to crystalline and amorphous secondary structures, respectively. This may be due to the DC having not undergone any prior SS removal process, shows an amorphous random form 21 , 22 . Although there were no significant differences between the chemical and autoclave degummed samples, a decrease in the β-turn structure was observed.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the modification of SF is necessary to improve its performance as well as be endowed with some above special functions. [7][8][9] The modified SF obtained by physical modification [10,11] and chemical modification [12,13] can effectively solve the above problems, and can be further spun into the modified SF fibers by dry spinning, wet spinning, electrospinning or microfluid spinning to be used in filtration, sensors, triboelectric nanogenerators, and tissue engineering, as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%